NECESIDAD DE REFORMAR EL TRÁMITE JUDICIAL ESTABLECIDO EN LA LEY DE MIGRACIÓN QUE ESTABLEZCA PROCEDIMIENTOS PARA LA DEPORTACIÓN QUE SE AJUSTEN A LA NORMATIVA CONSTITUCIONAL Y A LOS CONVENIOS Y TRATADOS INTERNACIONALES DE LOS QUE ECUADOR ES PARTE Y NO CONTRADIGAN EL PRINCIPIO DE CIUDADANIA UNIVERSAL - Mendieta Pacheco, Nathaly María (2016)
Human Mobility is part of the person since ancient times, we can say that is innate in him as is done with the aim of improving their quality of life. What the individual can not get into the territory in which it is seeking in other destinations. It is for this reason that migration is a global phenomenon and is present in all periods of history and in all parts of our planet. These population movements require states to enact laws regulating such movements, in addition to signing international treaties in order to safeguard the fundamental rights of people in situations of mobility and improve their living conditions. Shared responsibility between countries must be respect for human rights, ie the countries of origin, transit and destination to look for them for their immigrant ensuring equal rights for emigrants solutions required. In this context, Ecuador in its constitution establishes the principle of universal citizenship in Art. 416 in which he advocated. Ecuador is not the only country to free movement enshrined in its Constitution, then, other countries do, in the case of Argentina, Costa Rica, Peru, among others. The Constitution of the Republic of Ecuador in its Article 392 states that "ensure the rights of people in human mobility and exercises guidance of migration policy through the competent body". On this basis it requires the State to improve their immigration law, with the very spirit of harmony exists between the Constitution and the Law on Migration. 6 The situation of immigrants is mostly critical and requires, as at any other time, the protection of the State and the host society, because it is in those circumstances where it is more vulnerable, because we must not forget that this group of people outside your country, because it is looking for a better future, has abandoned his family and is located in a territory in which surely has no support of any kind. So if we consider that the alien comes only with the desire to improve the quality of life for him and his family and is now in a judicial conflict that threatens the reach of your dreams and goals, why not raise an administrative procedure rather than a judicial one that will surely allow the subject to regularize their stay in the country and not go through a traumatic process as is the deportation process.